Zinc battery
Patent Information
- Application Number
- JP2020075509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-04-21
AI Technical Summary
【0011】 本発明によれば、優れた耐短絡性を得られる亜鉛電池を提供することができる。
Smart Images

Figure 0007630915000002 
Figure 0007630915000003 
Figure 0007630915000004
Abstract
Description
[Technical field]
[0001] The present invention relates to zinc batteries. [Background technology]
[0002] Nickel-zinc batteries, air-zinc batteries, silver-zinc batteries, etc. are known as zinc batteries using a zinc negative electrode. For example, nickel-zinc batteries are aqueous batteries using an aqueous electrolyte such as an aqueous potassium hydroxide solution, and therefore have high safety, and are known to have a high electromotive force for an aqueous battery due to the combination of a zinc electrode and a nickel electrode. Furthermore, nickel-zinc batteries have excellent input / output performance and low cost, so that the possibility of applying them to industrial applications (e.g., applications such as backup power sources) and automotive applications (e.g., applications such as hybrid automobiles) is being considered.
[0003] The charge and discharge reactions of a nickel-zinc battery proceed, for example, according to the following formula (discharge reaction: to the right, charge reaction: to the left). (Positive electrode)2NiOOH+2H2O+2e - → 2Ni(OH)2+2OH - (Negative electrode) Zn+2OH - → Zn(OH)2+2e -
[0004] As shown in the above formula, in zinc batteries, zinc hydroxide (Zn(OH)2) is produced by the discharge reaction. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, it becomes zinc tetrahydroxide ions ([Zn(OH)4] 2-) diffuses into the electrolyte. As a result, the negative electrode undergoes a morphological change (deformation) and the distribution of the charging current becomes uneven, causing zinc to precipitate locally on the negative electrode, resulting in the formation of dendrites (branched crystals). In zinc batteries, when dendrites grow due to repeated charging and discharging, they penetrate the separator and cause a short circuit, and the formation of the dendrites leads to a decrease in life performance. In such zinc batteries, there is a demand for improving the life performance. For example, Patent Document 1 discloses a technology for preventing internal short circuits between positive and negative electrodes caused by zinc dendrites by interposing a nickel-plated nonwoven fabric between the positive and negative electrodes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Unexamined Patent Publication No. 58-126665 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a zinc battery that can achieve excellent short-circuit resistance. [Means for solving the problem]
[0007] One aspect of the present invention provides a zinc battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator having a first porous body layer and a second porous body layer located between the first porous body layer and the positive electrode, the density of the second porous body layer being greater than the density of the first porous body layer.
[0008] In this zinc battery, the first porous layer preferably contains polyethylene, and the second porous layer preferably contains polypropylene.
[0009] The separator may further include a third porous layer located between the first porous layer and the negative electrode, and the density of the third porous layer may be greater than the density of the first porous layer. The third porous layer preferably contains polypropylene.
[0010] The zinc battery may be a nickel-zinc battery. Effect of the Invention
[0011] According to the present invention, a zinc battery having excellent short-circuit resistance can be provided. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of an electrode group of a zinc battery. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of an electrode group of a zinc battery. [Diagram 3] 1 is a graph showing the change in discharge capacity during cycle testing for zinc batteries according to examples and comparative examples. [Figure 4] 1 is an SEM image showing a cross section of a separator after a cycle test. [Diagram 5] 1 is an SEM image showing a cross section of a separator after a cycle test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0014] In this specification, the numerical range indicated by "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In addition, in this specification, the term "layer" includes a structure having a shape formed on the entire surface when observed as a plan view, as well as a structure having a shape formed on a part of the surface. In addition, in this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended effect of the process is achieved.
[0015] Examples of the zinc battery (e.g., zinc secondary battery) according to the present embodiment include a nickel-zinc battery, an air-zinc battery, a silver-zinc battery, etc. The basic configuration of the zinc battery according to the present embodiment may be the same as that of a conventional zinc battery.
[0016] A zinc battery according to an embodiment of the present invention comprises a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator having a first porous body layer and a second porous body layer disposed between the first porous body layer and the positive electrode, the density of the second porous body layer being greater than the density of the first porous body layer. This zinc battery has excellent short circuit resistance. The reason why such an effect is obtained is not clear, but the present inventor speculates as follows.
[0017] In zinc batteries, as described above, dendrites penetrate the separator and reach the positive electrode, causing a short circuit. On the other hand, in the zinc battery according to this embodiment, by using a separator in which a plurality of porous layers are laminated, zinc can be precipitated and captured between the porous layers, and the precipitated zinc can be prevented from reaching the positive electrode. Furthermore, when a low-density porous layer (first porous layer) and a higher-density porous layer (second porous layer) are used as the plurality of porous layers, tetrahydroxide zincate ions diffused from the negative electrode permeate the low-density porous layer, and the permeated ions are captured between the high-density porous layer. That is, the low-density porous layer makes it easier to introduce tetrahydroxide zincate ions between the layers of the plurality of porous layers, and the presence of the high-density porous layer makes it easier to block and precipitate zinc between the layers. Thus, in the zinc battery equipped with the separator of this embodiment, dendrites are less likely to penetrate the separator and reach the positive electrode, so that a short circuit is less likely to occur.
[0018] Below, a nickel-zinc battery will be described as an example of the zinc battery according to this embodiment.
[0019] The zinc battery according to the present embodiment includes, for example, a battery case, an electrolyte, and an electrode group (for example, an electrode plate group). The electrolyte and the electrode group are contained in the battery case. The zinc battery according to the present embodiment may be either before or after chemical formation.
[0020] The electrolytic solution contains, for example, a solvent and an electrolyte. Examples of the solvent include water (e.g., ion-exchanged water). Examples of the electrolyte include basic compounds, such as alkali metal hydroxides, such as potassium hydroxide (KOH), sodium hydroxide (NaOH), and lithium hydroxide (LiOH). The zinc battery according to this embodiment can be used as an alkaline zinc battery using an alkaline electrolyte. The electrolytic solution may contain components other than the solvent and the electrolyte, such as potassium phosphate, potassium fluoride, potassium carbonate, sodium phosphate, sodium fluoride, zinc oxide, antimony oxide, titanium dioxide, and the like.
[0021] The electrode group is composed of, for example, a positive electrode (positive electrode plate, etc.), a negative electrode (negative electrode plate, etc.), and a separator (porous body) arranged between the positive electrode and the negative electrode. FIG. 1 is a schematic cross-sectional view showing an electrode group of a zinc battery according to one embodiment. As shown in FIG. 1, the electrode group 100A includes a positive electrode 10, a negative electrode 20, and a separator 30A arranged between the positive electrode 10 and the negative electrode 20. In the electrode group 100A shown in FIG. 1, the separator 30A is in contact with both the positive electrode 10 and the negative electrode 20, but the separator may be in contact with either one of the positive electrode or the negative electrode. In other words, the separator may not be in contact with at least one of the positive electrode and the negative electrode. The electrode group may include a plurality of positive electrodes and negative electrodes, and in this case, the plurality of positive electrodes and negative electrodes are connected to each other, for example, by a strap.
[0022] The positive electrode 10 includes, for example, a positive electrode current collector 11 and a positive electrode material 12 supported by the positive electrode current collector 11 .
[0023] The positive electrode current collector 11 constitutes a conductive path for a current from the positive electrode material 12. The positive electrode current collector 11 has, for example, a flat plate shape, a sheet shape, or the like. The positive electrode current collector 11 may be a three-dimensional mesh-structured current collector constituted by foam metal, expanded metal, punching metal, felt-like material of metal fiber, or the like. The positive electrode current collector 11 is constituted by a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the positive electrode 10 (a material having an oxidation-reduction potential more noble than the reaction potential of the positive electrode 10, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize the substrate, etc.) can be used as such a material. In addition, in the positive electrode 10, a decomposition reaction of the electrolyte proceeds as a side reaction, generating oxygen gas, and a material with a high oxygen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the positive electrode current collector 11 include platinum; nickel; and metal materials (copper, brass, steel, etc.) plated with metals such as nickel.
[0024] The positive electrode material 12 may be in a layered form (positive electrode material layer). For example, a layer of the positive electrode material 12 may be formed on the positive electrode current collector 11, and when the positive electrode current collector 11 has a three-dimensional mesh structure, the positive electrode material 12 may be filled between the meshes of the positive electrode current collector 11.
[0025] The positive electrode material 12 contains a positive electrode active material. Examples of the positive electrode active material include nickel oxyhydroxide (NiOOH) and nickel hydroxide. The positive electrode material 12 contains, for example, nickel oxyhydroxide in a fully charged state and nickel hydroxide in an end-of-discharge state. The content of the positive electrode active material may be, for example, 50 to 95 mass% based on the total mass of the positive electrode material.
[0026] The positive electrode material 12 may contain additives. Examples of additives include binders, conductive agents, and expansion inhibitors. Examples of binders include hydrophilic or hydrophobic polymers, such as hydroxypropylmethylcellulose (HPMC), carboxymethylcellulose (CMC), sodium polyacrylate (SPA), and fluorine-based polymers (polytetrafluoroethylene (PTFE)). The content of the binder may be, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material. Examples of conductive agents include cobalt compounds (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.). The content of the conductive agent may be, for example, 1 to 20 parts by mass with respect to 100 parts by mass of the positive electrode active material. Examples of expansion inhibitors include zinc oxide. The content of the expansion inhibitor may be, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material.
[0027] The negative electrode 20 includes, for example, a negative electrode current collector 21 and a negative electrode material 22 supported by the negative electrode current collector 21 .
[0028] The negative electrode current collector 21 constitutes a conductive path for a current from the negative electrode material 22. The negative electrode current collector 21 has, for example, a flat plate shape, a sheet shape, or the like. The negative electrode current collector 21 may be a three-dimensional mesh-structured current collector made of foamed metal, expanded metal, punched metal, felt-like metal fiber, or the like. The negative electrode current collector 21 is made of a material having electrical conductivity and alkali resistance. As such a material, for example, a material that is stable even at the reaction potential of the negative electrode 20 (a material having an oxidation-reduction potential more noble than the reaction potential of the negative electrode 20, a material that forms a protective film such as an oxide film on the surface of the substrate in an alkaline aqueous solution to stabilize it, etc.) can be used. In addition, in the negative electrode 20, a decomposition reaction of the electrolyte proceeds as a side reaction, generating hydrogen gas, and a material with a high hydrogen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials constituting the negative electrode current collector 21 include zinc, lead, tin, and metal materials plated with a metal such as tin (copper, brass, steel, nickel, etc.).
[0029] The negative electrode material 22 may be in a layered form (negative electrode material layer). For example, a layer of the negative electrode material 22 may be formed on the negative electrode current collector 21, and when the negative electrode current collector 21 has a three-dimensional mesh structure, the negative electrode material 22 may be filled between the meshes of the negative electrode current collector 21.
[0030] In this embodiment, the negative electrode material 22 contains a negative electrode active material containing zinc. The negative electrode according to this embodiment may be either before or after chemical formation.
[0031] Examples of the negative electrode active material containing zinc include metallic zinc, zinc oxide, zinc hydroxide, etc. The negative electrode material 22 contains, for example, metallic zinc in a fully charged state, and contains zinc oxide and zinc hydroxide in an end-of-discharge state.
[0032] The content of the negative electrode active material is preferably in the following range based on the total mass of the negative electrode material. From the viewpoint of easily obtaining excellent battery performance, the content of the negative electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 75 mass% or more. From the viewpoint of easily obtaining excellent battery performance, the content of the negative electrode active material is preferably 95 mass% or less, more preferably 90 mass% or less, and even more preferably 85 mass% or less.
[0033] The negative electrode material 22 may contain additives other than the negative electrode active material. Examples of the additives include a binder and a conductive agent. Examples of the binder include polytetrafluoroethylene, hydroxyethyl cellulose, polyethylene oxide, polyethylene, and polypropylene. The content of the binder may be, for example, 0.5 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material. Examples of the conductive agent include an indium compound (such as indium oxide). The content of the conductive agent may be, for example, 1 to 20 parts by mass relative to 100 parts by mass of the negative electrode active material.
[0034] The separator is disposed between the positive electrode and the negative electrode, and is configured as a laminate in which a plurality of porous layers are laminated in the direction from the negative electrode to the positive electrode (or from the positive electrode to the negative electrode). The porous layer means a layer formed of a material having porosity. The separator configured of a plurality of porous layers has ion permeability while electrically insulating the positive electrode and the negative electrode.
[0035] As shown in FIG. 1, the separator 30A according to one embodiment has a first porous body layer 31 and a second porous body layer 32 located between the first porous body layer 31 and the positive electrode 10. The separator 30A can also be said to be a laminate of the first porous body layer 31 and the second porous body layer 32. The first porous body layer 31 is in contact with the negative electrode material 22 in the negative electrode 20, and the second porous body layer 32 is in contact with the positive electrode material 12 in the positive electrode 10. That is, the zinc battery according to this embodiment includes an electrode group 100A including the negative electrode current collector 21, the negative electrode material 22, the first porous body layer 31, the second porous body layer 32, the positive electrode material 12, and the positive electrode current collector 11 in this order.
[0036] At least one of the first porous layer 31 and the second porous layer 32 may not be in contact with the negative electrode material 22 or the positive electrode material 12. In other words, the first porous layer 31 may not be in contact with the negative electrode material 22, and the second porous layer 32 may not be in contact with the positive electrode material 12.
[0037] The first porous layer 31 and the second porous layer 32 (hereinafter collectively referred to as "porous layers 31, 32") may be formed of a material that satisfies the conditions of having resistance to oxidation on the positive electrode 10 side and reduction on the negative electrode 20 side, having alkali resistance, etc. The porous layers 31, 32 may be formed of an organic material (such as a resin material), an inorganic material, an organic-inorganic material, etc. Examples of the resin material include polyamide-based polymers (e.g., polyamide), olefin-based polymers (polyolefins), and nylon-based polymers (e.g., nylon). Examples of the inorganic material include oxides such as alumina, titania, and silicon dioxide; nitrides such as aluminum nitride and silicon nitride; and sulfates such as barium sulfate and calcium sulfate. Examples of the organic-inorganic material include porous coordination polymers (PCP / MOF). The first porous layer 31 and the second porous layer 32 may be formed of the same material, or may be formed of different materials. The method for producing the porous layers 31 and 32 is not particularly limited, and examples thereof include a wet method (phase separation method), a dry method (stretching and opening method), melt blowing, and electrospinning.
[0038] The porous body layers 31 and 32 may be formed of a material containing a resin material. The resin material may be, for example, polyolefin, fluorine-based polymer, cellulose-based polymer, polyimide, nylon, or the like. The porous body layers 31 and 32 are preferably formed of a resin material, more preferably a material containing a polyolefin, from the viewpoint of easily obtaining excellent short-circuit resistance. Examples of polyolefin include polypropylene including isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, etc., polyethylene, polybutene, polymethylpentene, ethylene propylene rubber, etc. The polyolefin is preferably at least one selected from the group consisting of polyethylene and polypropylene, from the viewpoint of high stability against the electrolyte and high oxidation resistance. The first porous body layer 31 and the second porous body layer 32 preferably contain different polyolefins from each other in order to make the densities (described in detail later) different from each other.
[0039] The first porous layer 31 preferably contains polyethylene from the viewpoint of making the density smaller than that of the second porous layer 32. The second porous layer 32 preferably contains polypropylene from the viewpoint of making the density larger than that of the first porous layer 31.
[0040] From the viewpoint of hydrophilization, the porous body layers 31, 32 may contain an anionic surfactant, a cationic surfactant, an amphoteric surfactant, a nonionic surfactant, or the like, and may be subjected to a surface treatment such as sulfonation treatment, fluorine gas treatment, acrylic acid graft polymerization treatment, corona discharge treatment, plasma treatment, or the like. By hydrophilizing the porous body layers 31, 32, they become more compatible with the electrolyte, and a sufficient current density is easily obtained. The hydrophilization treatment may be performed before or after the porous body layers 31, 32 are laminated.
[0041] In the separator 30A according to this embodiment, the density of the second porous layer 32 is greater than the density of the first porous layer 31, from the viewpoint of obtaining excellent short-circuit resistance in a zinc-based battery.
[0042] The density of the porous layers 31, 32 can be measured by the following method. The first porous layer 31 or the second porous layer 32 is cut out from the separator 30A and cut into a piece of 16 cm x 16 cm. The thickness of the cut first porous layer 31 or second porous layer 32 is measured to calculate the volume, the mass is measured, and the density (g / cm) is calculated from the obtained mass and volume. 3 ) can be obtained.
[0043] The ratio of the density of the second porous body layer 32 to the density of the first porous body layer 31 (density of the second porous body layer / density of the first porous body layer) is greater than 1, and preferably 1.05 or more, 1.1 or more, 1.2 or more, or 1.25 or more, from the viewpoint of easily obtaining excellent short-circuit resistance. The ratio of the density of the second porous body layer 32 to the density of the first porous body layer 31 (second porous body layer / first porous body layer) is preferably 1.5 or less, more preferably 1.4 or less, and even more preferably 1.3 or less, from the viewpoint of easily obtaining excellent output performance.
[0044] The density of the first porous layer 31 is preferably 0.35 g / cm3 from the viewpoint of easily obtaining excellent short-circuit resistance. 3 More preferably, 0.38 g / cm 3 More preferably, 0.4 g / cm 3 More preferably, it is 0.6 g / cm 3 Below, 0.57g / cm 3 Below 0.55g / cm 3 Below 0.5g / cm 3 or less than 0.45g / cm 3 The following is the result.
[0045] The density of the second porous layer 32 is preferably 0.45 g / cm3 from the viewpoint of easily obtaining excellent short-circuit resistance. 3 More preferably, 0.48 g / cm 3 More preferably, 0.5 g / cm 3 More preferably, it is 0.65 g / cm 3 Less than or equal to 0.6 g / cm 3 More preferably, 0.58 g / cm 3 The following is the result.
[0046] The thickness of the first porous layer 31 is preferably 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, 10 μm or more, 15 μm or more, or 17 μm or more from the viewpoint of easily obtaining excellent short-circuit resistance. The thickness of the first porous layer 31 is preferably 150 μm or less, 120 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less from the viewpoint of excellent battery performance such as discharge performance.
[0047] The thickness of the second porous layer 32 is preferably 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, 10 μm or more, 15 μm or more, or 17 μm or more from the viewpoint of easily obtaining excellent short-circuit resistance. The thickness of the second porous layer 32 is preferably 150 μm or less, 120 μm or less, 100 μm or less, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less from the viewpoint of excellent battery performance such as discharge performance.
[0048] The thickness of the separator 30A is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, from the viewpoint of easily obtaining excellent short-circuit resistance. The thickness of the separator 30A is preferably 300 μm or less, 150 μm or less, 100 μm or less, 80 μm or less, 60 μm or less, or 50 μm or less, from the viewpoint of excellent battery performance such as discharge performance.
[0049] The average pore diameter of the porous layers 31 and 32 is preferably 50 nm or more, more preferably 70 nm or more, and even more preferably 85 nm or more, from the viewpoint of excellent battery performance such as discharge performance. The average pore diameter of the porous layers 31 and 32 is preferably 120 nm or less, more preferably 100 nm or less, and even more preferably 90 nm or less, from the viewpoint of easily obtaining excellent short-circuit resistance. The average pore diameter of the porous layers 31 and 32 can be measured by a mercury porosimeter (for example, manufactured by Mictomeritics, product name: AutoPoreIV9510). The average pore diameter of the porous layers 31 and 32 can be adjusted by adjusting the manufacturing method of the porous layers 31 and 32.
[0050] In the zinc battery according to this embodiment, the separator has a first porous layer and a high-density second porous layer located between the first porous layer and the positive electrode, so that zinc can be precipitated between the low-density porous layer (first porous layer) and the high-density porous layer (second porous layer). As a result, this zinc battery has excellent short-circuit resistance.
[0051] Next, another embodiment of the electrode group will be described. Fig. 2 is a schematic cross-sectional view showing an electrode group of a zinc battery according to another embodiment. In Fig. 2, the same components as those of the electrode group 100A shown in Fig. 1 are given the same reference numerals, and overlapping descriptions will be omitted.
[0052] The electrode group 100B shown in FIG. 2 is different from the electrode group 100A in that the separator 30B further includes a third porous body layer 33 located between the first porous body layer 31 and the negative electrode 20. The separator 30B can also be said to be a laminate of the third porous body layer 33, the first porous body layer 31, and the second porous body layer 32. The third porous body layer 33 is in contact with the negative electrode material 22 in the negative electrode 20, and the second porous body layer 32 is in contact with the positive electrode material 12 in the positive electrode 10. That is, the zinc battery according to this embodiment includes an electrode group 100B including the negative electrode current collector 21, the negative electrode material 22, the third porous body layer 33, the first porous body layer 31, the second porous body layer 32, the positive electrode material 12, and the positive electrode current collector 11 in this order.
[0053] At least one of the third porous layer 33 and the second porous layer 32 may not be in contact with the negative electrode material 22 or the positive electrode material 12. In other words, the third porous layer 33 may not be in contact with the negative electrode material 22, and the second porous layer 32 may not be in contact with the positive electrode material 12.
[0054] The third porous body layer 33 may be formed of the same material as the above-mentioned first porous body layer 31 and second porous body layer 32. The third porous body layer 33 preferably contains a polyolefin different from that of the first porous body layer 31. The third porous body layer 33 preferably contains polypropylene in order to have a higher density than the first porous body layer 31.
[0055] The third porous layer 33, like the first porous layer 31 and the second porous layer 32, may contain an anionic surfactant or the like from the viewpoint of hydrophilization, and may be subjected to a surface treatment for hydrophilization as described above.
[0056] In the separator 30B of this embodiment, in order to obtain excellent short-circuit resistance in a zinc battery, the density of the second porous body layer 32 laminated on the positive electrode 10 side of the first porous body layer 31 is greater than the density of the first porous body layer 31. Furthermore, the density of the third porous body layer 33 laminated on the negative electrode 20 side of the first porous body layer 31 is greater than the density of the first porous body layer 31.
[0057] The ratio of the density of the third porous body layer 33 to the density of the first porous body layer 31 (density of the third porous body layer / density of the first porous body layer) is greater than 1, preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.25 or more, from the viewpoint of easily obtaining excellent short-circuit resistance. The ratio of the density of the third porous body layer 33 to the density of the first porous body layer 31 (density of the third porous body layer / density of the first porous body layer) is preferably 1.5 or less, more preferably 1.4 or less, and even more preferably 1.3 or less, from the viewpoint of easily obtaining excellent output performance.
[0058] The density of the third porous layer 33 is preferably 0.45 g / cm3 from the viewpoint of easily obtaining excellent short-circuit resistance. 3 More preferably, 0.48 g / cm 3 More preferably, 0.5 g / cm 3 More preferably, it is 0.65 g / cm 3 Less than or equal to 0.6 g / cm 3 More preferably, 0.58 g / cm 3 The following is the result.
[0059] The thickness of the third porous layer 33 may be the same as the thickness of the above-mentioned first porous layer 31 or second porous layer 32. The thickness of the separator 30B may be the same as the thickness of the above-mentioned separator 30A.
[0060] In the zinc battery including this electrode group 100B, zinc can be precipitated between the low-density porous layer (first porous layer) and the high-density porous layer (second porous layer), so that the short-circuit resistance is excellent. In addition, in this zinc battery, by further having the third porous layer 33, zinc can be further precipitated between the porous layers (between the first and third porous layers, and between the first and third porous layers), so that the above effect can be further enhanced and the short-circuit resistance is further excellent.
[0061] The zinc battery described above may have further other embodiments. The zinc battery according to other embodiments may include, for example, a separator having other layers in addition to the above-mentioned first porous body layer, second porous body layer, and in some cases, third porous body layer. The other layer may be laminated so as to be located between the first porous body layer (or the third porous body layer) and the negative electrode, or may be laminated so as to be located between the second porous body layer and the positive electrode. The other layer may be an intermediate layer laminated between the first porous body layer and the second porous body layer, or between the first porous body layer and the third porous body layer.
[0062] The other layer may be a porous layer formed of the above-mentioned materials, or may be a nonwoven fabric made of fibers such as cellulose fibers, aramid fibers, and glass fibers.
[0063] In addition, a zinc battery according to yet another embodiment may have a separator in which a first porous body layer and a second porous body layer located between the first porous body layer and a positive electrode are repeatedly stacked (for example, two layers of each layer). In this case, for example, the zinc battery is provided with an electrode group including a negative electrode current collector, a negative electrode material, a first porous body layer, a second porous body layer, a first porous body layer, a second porous body layer, a positive electrode material, and a positive electrode current collector in this order. Alternatively, the zinc battery may be provided with an electrode group including a negative electrode current collector, a negative electrode material, a second porous body layer, a first porous body layer, a first porous body layer, a second porous body layer, a positive electrode material, and a positive electrode current collector in this order.
[0064] The manufacturing method of the nickel-zinc battery according to this embodiment includes, for example, an electrode manufacturing process for obtaining electrodes (positive and negative electrodes), a separator preparation process for preparing a separator, and an assembly process for assembling components including the electrodes and the separator to obtain a nickel-zinc battery.
[0065] In the electrode manufacturing process, positive and negative electrodes are manufactured. For example, a solvent (e.g., water) is added to the raw materials of the electrode materials (positive and negative electrode materials) and kneaded to obtain a paste-like electrode material (electrode material paste), and then the electrode material paste is used to form an electrode material layer.
[0066] The raw materials for the positive electrode material include raw materials for the positive electrode active material (e.g., nickel hydroxide), additives (e.g., the binder), etc. The raw materials for the negative electrode material include raw materials for the negative electrode active material (e.g., zinc metal, zinc oxide, and zinc hydroxide), additives (e.g., the binder), etc.
[0067] As a method for forming the electrode material layer, for example, an electrode material paste may be applied or filled onto a current collector, and then dried to obtain an electrode material layer. The density of the electrode material layer may be increased by pressing or the like, as necessary.
[0068] In the separator preparation step, a separator is prepared in which at least the first porous body layer and the second porous body layer having a density greater than that of the first porous body layer are laminated. The separator may be a commercially available product in which these porous body layers are laminated in advance, or may be manufactured by preparing the first porous body layer, the second porous body layer, and possibly other layers (such as a third porous body layer) and laminating these multiple porous body layers.
[0069] A method for laminating a plurality of porous body layers may include a method in which the porous body layers are laminated together by pressure bonding, or a method in which the porous body layers are laminated together via an adhesive such as polyvinyl alcohol.
[0070] In the assembly process, for example, first, the positive electrodes and negative electrodes obtained in the electrode manufacturing process are alternately stacked with the separator obtained in the separator preparation process interposed therebetween, and the positive electrodes and the negative electrodes are connected with straps to prepare an electrode group. Next, this electrode group is placed in a battery container, and a lid is attached to the top surface of the battery container to obtain an unformed nickel-zinc battery. When stacking the electrodes and the separator, the first porous layer of the separator is stacked on the negative electrode side, and the second porous layer is stacked on the positive electrode side. Even when other layers are stacked on the separator, the positional relationship between the first porous layer and the second porous layer is the same.
[0071] Next, the electrolyte is poured into the battery case of the unformed nickel-zinc battery and left for a certain period of time. Next, the battery is formed by charging under predetermined conditions to obtain a nickel-zinc battery. The formation conditions can be adjusted according to the properties of the electrode active materials (positive and negative active materials).
[0072] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. For example, in the above embodiment, an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode has been described, but the zinc battery may be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode.
[0073] The air electrode of the air zinc battery can be a known air electrode used in air zinc batteries. The air electrode includes, for example, an air electrode catalyst, an electron conductive material, etc. The air electrode catalyst can be an air electrode catalyst that also functions as an electron conductive material.
[0074] As the air electrode catalyst, one that functions as a positive electrode in an air zinc battery can be used, and various air electrode catalysts that can utilize oxygen as a positive electrode active material can be used. Examples of the air electrode catalyst include carbon-based materials (graphite, etc.) having an oxidation-reduction catalytic function, metal materials (platinum, nickel, etc.) having an oxidation-reduction catalytic function, and inorganic oxide materials (perovskite-type oxides, manganese dioxide, nickel oxide, cobalt oxide, spinel oxide, etc.) having an oxidation-reduction catalytic function. The shape of the air electrode catalyst is not particularly limited, and may be, for example, particulate. The content of the air electrode catalyst in the air electrode may be 5 to 70 volume %, 5 to 60 volume %, or 5 to 50 volume % relative to the total volume of the air electrode.
[0075] As the electron conductive material, a material that has electrical conductivity and enables electron conduction between the air electrode catalyst and the separator can be used. Examples of the electron conductive material include carbon blacks such as ketjen black, acetylene black, channel black, furnace black, lamp black, and thermal black; graphites such as natural graphite such as flake graphite, artificial graphite, and expanded graphite; conductive fibers such as carbon fibers and metal fibers; metal powders such as copper, silver, nickel, and aluminum; organic electron conductive materials such as polyphenylene derivatives; and any mixtures thereof. The shape of the electron conductive material may be particulate or may be other shapes. The electron conductive material is preferably used in a form that provides a continuous phase in the thickness direction in the air electrode. For example, the electron conductive material may be a porous material. The electron conductive material may also be in the form of a mixture or complex with the air electrode catalyst, and may be an air electrode catalyst that also functions as an electron conductive material as described above. The content of the electronically conductive material in the air electrode may be 10 to 80% by volume, 15 to 80% by volume, or 20 to 80% by volume relative to the total volume of the air electrode.
[0076] As the silver oxide electrode of the silver-zinc battery, a known silver oxide electrode used in silver-zinc batteries can be used. The silver oxide electrode includes, for example, silver(I) oxide. EXAMPLES
[0077] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0078] <Example 1> [Preparation of electrolyte] Potassium hydroxide (KOH) and lithium hydroxide (LiOH) were added to ion-exchanged water and mixed to prepare an electrolyte solution (potassium hydroxide concentration: 30 mass %, lithium hydroxide concentration: 1 mass %).
[0079] [Preparation of negative electrode] A tin-plated steel punching metal with an aperture ratio of 60% was prepared as a negative electrode current collector. Next, zinc oxide, zinc metal, PTFE, and ion-exchanged water were weighed in predetermined amounts and mixed, and the resulting mixture was stirred to prepare a negative electrode material paste. At this time, the mass ratio of the solid contents was adjusted to "zinc oxide:zinc metal:PTFE=80:15:5". The moisture content of the negative electrode material paste was adjusted to 32.5 mass% based on the total mass of the negative electrode material paste. Next, the negative electrode material paste was applied onto the negative electrode current collector, and then dried at 80°C for 30 minutes. Thereafter, it was pressure-molded with a roll press to obtain a negative electrode material paste having a density of 3.5 g / cm. 3 Thus, an unformed negative electrode having a negative electrode material (negative electrode material layer) was obtained.
[0080] [Preparation of positive electrode] A nickel foam with a porosity of 90% was prepared as a positive electrode current collector. Next, a predetermined amount of nickel hydroxide powder, metallic cobalt, cobalt hydroxide, CMC, PTFE, and ion-exchanged water were weighed and mixed, and the mixture was stirred to prepare a positive electrode material paste. At this time, the mass ratio of the solid content was adjusted to "nickel hydroxide: metallic cobalt: cobalt hydroxide: CMC: PTFE = 85: 8: 5: 1: 1". The moisture content of the positive electrode material paste was adjusted to 27.5 mass% based on the total mass of the positive electrode material paste. Next, the positive electrode material paste was applied onto the positive electrode current collector, and then dried at 80 ° C for 30 minutes. After that, it was pressure-molded with a roll press to obtain an unformed positive electrode having a positive electrode material layer.
[0081] [Preparing the separator] The separator is a laminate of a polyethylene (PE) porous membrane and a polypropylene (PP) porous membrane (density of the PE porous membrane: 0.543 g / cm 3 , Density of PP porous membrane: 0.600 g / cm 3 ) was used. The thickness of the laminate was 60 μm. This laminate was hydrophilized with a surfactant Triton-X100 (manufactured by Dow Chemical Co.) before assembling the battery. The hydrophilization was performed by immersing the separator in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, and then drying it at room temperature for 1 hour. Thereafter, the laminate was cut to a specified size, folded in half so that the surface on the polypropylene porous membrane side was on the inside, and processed into a bag shape.
[0082] [Preparation of nickel-zinc battery] A positive electrode housed in a laminate of a bag-shaped porous membrane, a negative electrode housed in a laminate of a bag-shaped porous membrane, and a nonwoven fabric (VL100, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) were stacked, and the plates of the same polarity were connected with a strap to prepare an electrode group (electrode plate group). The electrode group was configured with one positive electrode and two negative electrodes, with a nonwoven fabric placed between the positive and negative electrodes. After placing this electrode group in a battery case, a lid was attached to the top surface of the battery case to obtain an unformed nickel-zinc battery. Next, an electrolyte was poured into the battery case of the unformed nickel-zinc battery, and the battery was left for 24 hours. After that, charging was performed under the conditions of 60 mA and 15 hours, and a nickel-zinc battery with a nominal capacity of 600 mAh was prepared.
[0083] <Example 2> The separator is a laminate of a polypropylene (PP) porous film, a polyethylene (PE) porous film, and a polypropylene (PP) porous film stacked in this order (density of the PP porous film: 0.600 g / cm 3 , Density of PE porous membrane: 0.543g / cm 3) was used. The thickness of the laminate was 40 μm. After the laminate was hydrophilized by the above method, it was folded in half and processed into a bag shape. A nickel-zinc battery was produced in the same manner as in Example 1, except that this separator was used.
[0084] <Example 3> The separator is a laminate of a polypropylene (PP) porous film, a polyethylene (PE) porous film, and a polypropylene (PP) porous film stacked in this order (density of the PP porous film: 0.600 g / cm 3 , Density of PE porous membrane: 0.543g / cm 3 ) was used. The thickness of the laminate was 60 μm. After the laminate was hydrophilized by the above method, it was folded in half and processed into a bag shape. A nickel-zinc battery was produced in the same manner as in Example 1, except that this separator was used.
[0085] <Comparative Example 1> The separator is a porous polypropylene (PP) membrane (density: 0.600 g / cm 3 ) was used. The thickness of the porous membrane was 40 μm. After the laminate was hydrophilized by the above method, it was folded in half and processed into a bag shape. A nickel-zinc battery was produced in the same manner as in Example 1, except that this separator was used.
[0086] <Comparative Example 2> The separator has polyethylene A laminate consisting of two PE porous membranes (density of PE porous membrane: 0.543 g / cm 3 ) was used. The thickness of the laminate was 40 μm. After the laminate was hydrophilized by the above method, it was folded in half and processed into a bag shape. A nickel-zinc battery was produced in the same manner as in Example 1, except that this separator was used.
[0087] <Battery performance evaluation> The nickel-zinc batteries of the examples and comparative examples were used to evaluate cycle life performance and high rate discharge performance.
[0088] (Cycle life performance evaluation: short circuit resistance test) A test (25° C.) was carried out on the nickel-zinc battery, with the following operations (1) and (2) forming one cycle, and the discharge capacity of each cycle was measured. (1) Charge a nickel-zinc battery at 25°C, 600 mA (1C), and a constant voltage of 1.9 V until the current decays to 30 mA (0.05 C). (2) After (1), discharge the nickel-zinc battery at a constant current of 300 mA (0.5 C) until the battery voltage reaches 1.1 V. The cycle test was performed up to 500 cycles. The test was terminated when the discharge capacity fell below 50% of the initial discharge capacity. Table 1 shows the number of cycles at which the capacity retention rate reached 50%. This number was evaluated according to the following criteria. A: The number of cycles when the capacity retention rate reaches 50% is 500 or more. B: The number of cycles when the capacity retention rate reaches 50% is between 300 and 500 C: The number of cycles when the capacity retention rate reaches 50% is less than 300
[0089] Table 1 shows the capacity retention rate at the 200th cycle and the number of cycles performed until the end of the test. Figure 3 shows the change in discharge capacity during the cycle test. The vertical axis of Figure 3 shows the discharge capacity retention rate (%), and the horizontal axis shows the number of cycles. The discharge capacity retention rate was calculated using the following formula. Discharge capacity retention rate (%) = (discharge capacity at each cycle) / (initial discharge capacity) x 100
[0090] The "C" above is a relative expression of the magnitude of the current when discharging the rated capacity at a constant current from a fully charged state. "C" means "discharge current value (A) / battery capacity (Ah)". For example, a current that can discharge the rated capacity in 1 hour is expressed as "1C", and a current that can discharge the rated capacity in 2 hours is expressed as "0.5C".
[0091] [Table 1]
[0092] In the cycle life performance evaluation, the number of cycles when the capacity retention rate reached 50% and the capacity retention rate at the 200th cycle were comprehensively evaluated. The cycle life performance was ranked from A to B in order of excellence, and the results of the comprehensive evaluation are shown in Table 1. As shown in Table 1, the nickel-zinc batteries of Examples 1 to 3 have a well-balanced and excellent cycle number when the capacity retention rate reached 50% and the cycle number at the 200th cycle, so that it can be said that the cycle life performance is excellent. On the other hand, the nickel-zinc battery of Comparative Example 1 had a significantly smaller cycle number when the capacity retention rate reached 50% than those of Examples 1 to 3, so that it was judged to be inferior in the comprehensive evaluation. In addition, the nickel-zinc battery of Comparative Example 2 had a poor capacity retention rate at the 200th cycle, and the cycle number when the capacity retention rate reached 50% was also rated B, so that it was judged to be inferior in the comprehensive evaluation.
[0093] <Evaluation of separator cross section> A separator was taken from the nickel-zinc battery of Example 2, and the cross section of the separator was observed with a scanning electron microscope (SEM). The results are shown in Figures 4 and 5. In the images in Figures 4 and 5, the upper part of the image is the porous membrane arranged on the negative electrode side, and the lower part of the image is the porous membrane arranged on the positive electrode side. As shown in Figure 4, zinc was precipitated and captured between the PP porous membrane arranged on the negative electrode side and the PE porous membrane. In addition, as shown in Figure 5, zinc was precipitated and captured between the PP porous membrane arranged on the positive electrode side and the PE porous membrane. Therefore, it is considered that by using this separator, dendrites generated by the precipitation of zinc penetrate the separator, and the battery is short-circuited. [Explanation of symbols]
[0094] Reference Signs List 10... positive electrode, 11... positive electrode current collector, 12... positive electrode material, 20... negative electrode, 21... negative electrode current collector, 22... negative electrode material, 30A, 30B... separator, 31... first porous layer, 32... second porous layer, 33... third porous layer, 100A, 100B... electrode group.
Claims
1. A positive electrode and A negative electrode; a separator disposed between the positive electrode and the negative electrode, the separator has a first porous layer and a second porous layer located between the first porous layer and the positive electrode, the density of the second porous layer is greater than the density of the first porous layer; a ratio of the density of the second porous layer to the density of the first porous layer is greater than 1 and is not greater than 1.5; A zinc battery, wherein the separator has a thickness of 150 μm or less.
2. The zinc battery of claim 1 , wherein the first porous layer comprises polyethylene and the second porous layer comprises polypropylene.
3. the separator further has a third porous layer located between the first porous layer and the negative electrode, The zinc battery according to claim 1 or 2, wherein the density of the third porous layer is greater than the density of the first porous layer.
4. The zinc battery of claim 3 , wherein the third porous layer comprises polypropylene.
5. The zinc battery according to any one of claims 1 to 4, which is a nickel-zinc battery.
Citation Information
Patent Citations
Alkaline battery
JP1982095068A
Nickel zinc battery
JP1983126665A
Alkaline zinc storage battery
JP1987117259A
Lithium secondary battery
JP1989027158A
Alkaline cell
JP1989173567A